Universal Design Analysis At Roemani Hospital, Semarang City - Munana, Mifta Nila; Widiastuti, Kurnia (International Journal of Sustainable Building, Infrastructure and Environment (IJOSBIE), 2026)
Abstract. Hospitals are always developing their services in every sector, including support facilities for patients and hospital users. One of hospital in Semarang that is undergoing development is Roemani Hospital. Many visitors come to this hospital because of its good service and adequate facilities. The research was conducted by observing the emergency unit in the Adam Building. The results of the identification will be analyzed based on regulations and principles of universal design. The results of the analysis of the implementation of universal design in the Adam Building will serve as a reference for the hospital to become one of the hospitals that implements universal design well and also for improvements if the analysis results are not satisfactory. The application of universal design aims to be accessible to all users regardless of age, physical limitations, and other factors.Keywords: Universal Desain, Disability, Public Area, Hospital